SOCIETY - THE COERCIVE FORCE: A LITERARY STUDY OF HENRIK IBSEN’S A DOLL’S HOUSE AND GHOSTS - Dr. Rafiq Nawab; Sania Gul; Sana Amin (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper examines the social limitations realized in Henrik Ibsen’s plays A Doll’s House and Ghosts, which not only end the pleasures of life but also bring his protagonists to the status of ‘nonbeing’ (meaningless existence). Consequently, this status of ‘nonbeing’ drives them to drastic and desperate actions. They are filled with frights and terrors, become rebellious, and undertake extreme steps, which not only ruin their own lives but others as well. Ibsen’s protagonists (chiefly women) possessed by aspirations and emotional desires, confronted by social limitations, cannot create a world, where they can assert their own individuality and freedom. These limitations create disorder and chaos and prove to be the unconquerable obstacles in their lives. Ultimately the protagonists find themselves involved in a series of conflicts and troubles which almost always bring ruin to them and force them to injure others. Either they strive to overcome these limitations, or succumb to them, in both cases, they suffer. In the face of these limitations, life becomes meaningless and unbearable for them. The movement of the study follows the pattern of discussion and analysis. This study is a literary research based on primary (text of the plays) and secondary (criticism of the plays) sources, using close reading analytical research design.